Getting to Equal : Promoting Gender Equality through Human Development - World Bank (Washington, DC, 2017)
To achieve gender equality and empower women, it is essential to invest in human development. The World Development Report 2012: Gender Equality and Development (hereafter WDR 2012) brings the best global evidence to bear on the relationship between gender equality and development. A central theme running through the report is how investments and outcomes in human development namely health, education, social protection, and labor shape, and are shaped by, gender equality. This note is designed as a companion to the WDR 2012 and highlights some of the World Bank Group's recent experience with and impact on promoting gender equality through its work in human development. Gender equality benefits society as a whole. Greater gender equality today shapes the norms and cultures as well as the constraints and possibilities of tomorrow's men and women. A wealth of evidence demonstrates that gender equality begins a virtuous circle of higher productivity, lower poverty, and better development outcomes for generations to come.